Measuring the mismatch between field of study and occupation using a task-based approach - Maurício Cortez Reis (Journal for Labour Market Research, 2018)
This paper seeks to provide a continuous measure to represent the distance between skills acquired in tertiary education and those required in an individual's occupation. This distance measure, which is computed by combining data from the 2010 Brazilian census with information from the 2010 Brazilian classification of occupations, suggests that workers usually classified in most of the literature into a single group of mismatches are in fact quite heterogeneous in the way their occupations are associated with areas of study. Evidence also shows that, even among mismatched workers, hourly labor earnings tend to decrease as the distance measure increases. This indicates the labor earnings penalty is not the same for all mismatched workers, seemingly changing substantially depending on the level of similarity between occupation and field of study.
Keywords: J24; J31; I26; 330; Occupations; Fields of study; Skill requirements